THE EFFECT OF ADDING VARIOUS TYPES OF ANTIOXIDANT MATERIALS ON THE MOTILITY AND VIABILITY OF BULL SEMEN: A LITERATURE RIVIEW - Zein, Moch Dea; Ali, Dzul Himam Isnan; Fatkhurohman, Muhammad; Tjahajati, Ida; Ridlo, Muhammad Rosyid (Buletin Veteriner Udayana; Vol. 15 No. 5 October 2023, 2023)
The quality of the cement used for Artificial Insemination (AI) influences the success of AI. The quality of frozen semen can be maintained by adding diluents that contain nutrients to maintain the viability of spermatozoa, prevent cold shock during freezing, and maintain the same osmotic pressure and pH as sperm cells. Spermatozoa also require antioxidants to protect against damage due to reactive oxygen species (ROS). This research aims to determine various types of antioxidants on the motility and viability of spermatozoa from cow semen. The method we use is a literature study which summarizes several pieces of literature whose library sources come from journals and articles searched via Google Scholar. Library sources are selected based on their correlation with the title of the literature study being reviewed. The research results show that the use of green tea antioxidants which contain EGCG, virgin coconut oil and commercial vitamin E which contains tocopherol, genistein with isoflavone content, fish oil with omega 3 content can inhibit lipid peroxidation and provide cell protection against oxidative damage from ROS. The results of the previous literature study certainly still require a lot of development. Therefore, further testing can be carried out to check the accuracy of the research data.